'Crazy Monkey' Poisons Man and Dog: Human and canine seizures due to PB-22, a novel synthetic cannabinoid. (July 2014) - Gugelmann, H.; Gerona, R.; Li, C.; Tsutaoka, B.; Olson, K. R.; Lung, D.
Abstract Context. Synthetic cannabinoids have been manufactured, sold, and consumed for recreational purposes since at least 2004; their use has been associated with adverse psychiatric, cardiovascular, renal, pulmonary, and neurologic effects. We report simultaneous canine and human clinical cases associated with exposure to a novel synthetic cannabinoid, PB-22 (QUPIC). Case report. A 22-year-old man brought his dog to a veterinary clinic after it had a seizure. During the course of the canine's evaluation, the human patient was witnessed to have a generalized tonic–clonic seizure. He was intubated for agitation and combativeness after his arrival to the emergency department (ED). He was extubated the next day without discernable sequelae. The canine patient received intravenous hydration and was also discharged to home after a period of close observation. The man later endorsed smoking three containers of a substance called "Crazy Monkey" daily for several weeks, but would not disclose how his dog had been exposed. The convulsant effects of "Crazy Monkey" were confirmed in this patient when, three months later, he was sedated, paralyzed, intubated, and admitted to another local hospital for seizures in the context of smoking the same product. Discussion. Laboratory analysis of samples obtained from the human and canine patients. A sample of the product (labeled "Crazy Monkey") revealed the presence of PB-22 (QUPIC), a novel synthetic cannabinoid. Additionally, serum and urine samples from the human patient contained metabolites of a second compound, UR-144. Conclusion. We present a laboratory-confirmed case report of human and canine neurotoxicity associated with a novel synthetic cannabinoid, PB-22 (QUIPIC).